Psychometric Evaluation of the Symptoms of Dementia Screener (SDS) in a Geriatric Primary Care Population. Issue 5 (20th October 2019) - Flaherty, Lauren B.; Midden, Allison; Mast, Benjamin T.
ABSTRACT: Objectives : The Symptoms of Dementia Screener (SDS) is an 11-item scale developed to screen for cognitive impairment. We aim to evaluate the psychometric properties of the SDS for use in primary care. Methods : We analyzed data from 192 patients: 25 not impaired, 42 with mild cognitive impairment (MCI), and 125 with dementia. Cronbach's reliability, convergent validity, and clinical utility were examined. The SDS was investigated at the item level using binary two-parameter model item response theory (IRT) techniques. Results : The SDS demonstrated good reliability (11 items; α = .74). We found negative correlations between SDS and the Mattis DRS-2 (r = −.523, p  < .01). Receiver operating characteristic (ROC) curves demonstrated acceptable clinical utility for detecting MCI and dementia with sensitivities and specificities of 83% and 52% for MCI; 78.4% and 84% for dementia, and 91% and 52% for any impairment. IRT analyses revealed 10 out of 11 items were moderately to very highly related to underlying latent factors of impairment. Conclusions : The SDS demonstrates good psychometric properties and is useful for detecting cognitive impairment in primary care settings. Clinical Implications : The SDS is an effective screening tool that does not require special training for its use in primary care. A positive screen indicates a need for further cognitive testing.